Mental well-being of patients with stages 0-2 of knee osteoarthritis after orthovoltage radiotherapy: open randomized trial evaluating quality of life - Maria V. Makarova; Mikhail Yu. Valkov; Lyubov A. Kuznetsova (Russian Open Medical Journal)
Objective — To compare the mental component of the quality of life (QOL) in patients with stages 0-2 of knee osteoarthritis (OA) sensu Kellgren-Lawrence after treatment either with symptomatic slow-acting drugs for osteoarthritis (SYSADOA) and non-steroidal anti-inflammatory drugs (NSAIDs), or with SYSADOA, NSAIDs and orthovoltage radiotherapy (OVRT), in an open randomized study, using the SF-36 questionnaire. Material and Methods — The patients were randomly assigned to two groups: SYSADOA and SYSADOA+OVRT. Patients were asked to fill out the SF-36 questionnaire. The results were presented in the form of a mean of scores on each of four QOL survey sections for both groups at five time points: before and immediately after the treatment, at 6 months, 12 months and 36 months. Results — The groups were similar in their baselines characteristics (age, gender, body mass index [BMI], pain syndrome duration). Being initially equal, QOL improved by the end of treatment in both groups with statistically significantly greater improvement after OVRT. Further on, the QOL indicators in the OVRT group kept increasing, peaking at 12 months for social role functioning (SRF), emotional role functioning (ERF) and vitality (V), and at 36 months for mental health (MH). In contrast, the patients of SYSADOA/NSAIDs group were experiencing a decrease in their mental component over the analyzed period of time, and the levels of three out of four indicators at 36 months were even lower than their initial values. Conclusion — Adding OVRT to the standard SYSADOA/NSAIDs treatment for knee OA of stages 0-2 ensured improved mental well-being of patients for at least three years.